A Low‐Symmetry Dysprosium Metallocene Single‐Molecule Magnet with a High Anisotropy Barrier. (27th July 2016) - Pugh, Thomas; Chilton, Nicholas F.; Layfield, Richard A.
Abstract: The single‐molecule magnet (SMM) properties of the isocarbonyl‐ligated dysprosium metallocene [Cp*2 Dy{μ‐(OC)2 FeCp}]2 (1Dy ), which contains a rhombus‐shaped Dy2 Fe2 core, are described. Combining a strong axial [Cp*] − ligand field with a weak equatorial field consisting of the isocarbonyl ligands leads to an anisotropy barrier of 662 cm −1 in zero applied field. The dominant thermal relaxation pathways in1Dy involves at least the fourth‐excited Kramers doublet, thus demonstrating that prominent SMM behavior can be observed for dysprosium in low‐symmetry environments.